Competition and resource breadth shape niche variation and overlap in multiple trophic dimensions. Issue 1902 (1st May 2019) - Costa-Pereira, Raul; Araújo, Márcio S.; Souza, Franco L.; Ingram, Travis
Abstract : Competition plays a central role in the maintenance of biodiversity. A backbone of classic niche theory is that local coexistence of competitors is favoured by the contraction or divergence of species' niches. However, this effect should depend on the diversity of resources available in the local environment, particularly when resources vary in multiple ecological dimensions. Here, we investigated how available resource breadth (i.e. prey diversity) and competition together shape multidimensional niche variation (between and within individuals) and interspecific niche overlap in 42 populations of congeneric tropical frog species. We modelled realized niches in two key trophic dimensions (prey size and carbon stable isotopes) and sampled available food resources to quantify two-dimensional resource breadth. We found a 14-fold variation in multidimensional population niche width across populations, most of which was accounted for by within-individual diet variation. This striking variation was predicted by an interaction whereby individual niche breadth increased with resource breadth and decreased with the number of congeneric competitors. These ecological gradients also interact to influence the degree of niche overlap between species, which surprisingly decreased with population total niche width, providing novel insights on how similar species can coexist in local communities. Together, our results emphasize that patterns of exploitation of resources in multiple dimensions are driven by both competitive interactions and extrinsic factors such as local resource breadth.